2021
DOI: 10.1249/mss.0000000000002753
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Hamstring Fatigue and Sprint Kinematics during a Simulated Football (Soccer) Match

Abstract: Purpose: Neuromuscular fatigue is considered to be important in the etiology of hamstring strain injuries in football. Fatigue is assumed to lead to decreases in hamstring contractile strength and changes in sprinting kinematics, which would increase hamstring strain injury risk. Therefore, the aim was to examine the effects of football-specific fatigue on hamstring maximal voluntary torque (MVT) and rate of torque development (RTD), in relation to alterations in sprinting kinematics. Methods: Ten amateur foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…These results clearly show the importance of the individual characteristics of each person in their responses to fatigue. Indeed, two other studies have also described the impact of fatigue on the knee joint [ 72 , 73 ]. The two studies mentioned above showed opposite results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly show the importance of the individual characteristics of each person in their responses to fatigue. Indeed, two other studies have also described the impact of fatigue on the knee joint [ 72 , 73 ]. The two studies mentioned above showed opposite results.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies mentioned above showed opposite results. In fact, Wilmes et al (2021) [ 72 ] reported an increase in peak knee extension, while Baumert et al (2021) [ 73 ] showed a decrease in peak knee extension during fatigue. In the present study, some athletes adopted a movement pattern that would protect them from hamstring strain, but others showed body arrangements that potentially increased this strain and in turn probably their risk of hamstring injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of this value, on the other hand, represents a relevant indicator for hamstring injury risk reducing (Śliwowski et al, 2015;Mendiguchia et al, 2012): it allows us to understand the effects of peripheral fatigue deriving from sport-specific exercises and the performance relationships (Wilmes et al, 2021;Castillo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion of sport-specific exercises rather than general ones (which are easier to control in terms of intensity and volume) could lead to an overload on some muscle groups that are most frequently engaged in soccer ability (Madison et al, 2019;Wilmes et al, 2021;Ekstrand et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation